The Leader of Human Immunodeficiency Virus Type 1 Genomic RNA Harbors an Internal Ribosome Entry Segment That Is Active during the G(2)/M Phase of the Cell Cycle - Brasey, Ann (American Society for Microbiology, 2003)
The 5′ leader of the human immunodeficiency virus type 1 (HIV-1) genomic RNA contains highly structured domains involved in key steps of the viral life cycle. These RNA domains inhibit cap-dependent protein synthesis. Here we report that the HIV-1 5′ leader harbors an internal ribosome entry site (IRES) capable of driving protein synthesis during the G(2)/M cell cycle phase in which cap-dependent initiation is inhibited. The HIV-1 IRES was delineated with bicistronic mRNAs in in vitro and ex vivo assays. The HIV-1 leader IRES spans nucleotides 104 to 336 and partially overlaps the major determinants of genomic RNA packaging. These data strongly suggest that, as for HIV-1 transcription, IRES-mediated translation initiation could play an important role in virus replication during virus-induced G(2)/M cell cycle arrest.